Improving Students’ Grammar Competences in Writing Descriptive Text Through Community Language Learning (Cll) Method - Munir AP, Muhammad Misbahul (Institut Agama Islam Negeri Kudus, 2019)
This research aims at identifying: (1) whether and to what extent Community Language Learning (CLL) method can improve students’ grammar competences in writing descriptive text, and explain (2) the class situation when Community Language Learning (CLL) method is used in teaching grammar in writing descriptive text. The students in the first year of junior high school have difficulty in their grammar competences that causes many errors in writing descriptive text. The classroom action research was conducted in two cycles. The research findings show that: (1) Community Language Learning (CLL) method can improve the students’ grammar competences in writing descriptive text, and (2) Community Language Learning (CLL) method provides enjoyment to support the effective classroom situation when used to teach grammar in writing descriptive text. This method can be an alternative method for the teacher or the future researchers who will conduct the similar research.